Improving Passing Skills In Volleyball Games For Students Of It Bina Insan Batang Middle School Quiz - Muhammad Azzam Taqiyyuddin; Wiwik Kusmawati (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
Based on the results of observations at SMP IT Bina Insan Batang Kuis, researchers still found several students who did not understand the skills of several passing techniques in volleyball so that the game seemed haphazard. This was possibly caused by the students' inability to master passing. This study used the classroom action research (CAR) method. Generally speaking, in classroom action research, there are four stages that are commonly passed, namely, (1) planning, (2) action, (3) observation, (4) reflection. From the results of the study, it can be concluded that there was an increase in passing skills in students at SMP IT Bina Insan Batang Kuis.